(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this article, we study some results around the first eigenvalue λ_1,m for the partial discrete Dirichlet boundary value problem, like the constant sign of the eigenfunction associated with λ_1,m, the simplicity of λ_1,m and the sign change of any eigenfunction associated with λ > λ_1,m.